2018
DOI: 10.3390/machines6030042
|View full text |Cite
|
Sign up to set email alerts
|

Study on Surface Roughness of Gcr15 Machined by Micro-Texture PCBN Tools

Abstract: This paper applies micro textures to the rake face of PCBN (Polycrystalline Cubic Boron Nitride) tools, including three types of micro textures that are microgroove textures vertical to the cutting edge, microgroove textures parallel to the cutting edge, and microhole textures. In this paper, the effects of different cutting speeds on the surface quality of hardened bearing steel GCr15 by dry turning with non-texture PCBN tools and micro-texture PCBN tools are studied, and the surface roughness values obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…On the contrary, the flow density of fast argon atoms arriving at the reamer from the grid (Figure 3) is distributed on its surface quite homogeneously. Sputtering by the fast atoms results in removal from the cutting edge and neighboring surface [45,46] of a layer with uniform thickness, which should result in the tool sharpening [47]. Figure 5b demonstrates profiles of the reamer cutting edges, their width w, and height h being measured in µm, prior to the processing (on the left) as well as after sharpening and nitriding (in the middle).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the flow density of fast argon atoms arriving at the reamer from the grid (Figure 3) is distributed on its surface quite homogeneously. Sputtering by the fast atoms results in removal from the cutting edge and neighboring surface [45,46] of a layer with uniform thickness, which should result in the tool sharpening [47]. Figure 5b demonstrates profiles of the reamer cutting edges, their width w, and height h being measured in µm, prior to the processing (on the left) as well as after sharpening and nitriding (in the middle).…”
Section: Resultsmentioning
confidence: 99%
“…With the development of the manufacturing industry, the texturization of cutting tools has become a new research direction and hotspot in the field of machining. Numerous studies have demonstrated that machining microns or nanoarrays of various shapes, distributions and sizes on the rake (back) face of tools can decrease cutting force (Deng et al , 2014; Liu et al , 2019), cutting temperature (Qi et al , 2011), friction coefficient (Kim et al , 2016; Gajrani et al , 2016), tool life (Li et al , 2019a; Sasi et al , 2017) and surface quality (Pan et al , 2018; Zhang et al , 2020). In addition, some researchers have investigated the effect of microtexture tools on chip formation and have discovered that machining microtexture on the rake tool face can change the tool chip contact state, subsequently influencing chip formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some scholars observed and studied the surface morphology of earthworms [8], pangolins [9], snakes [10], fishes [11], snails [12], and other organisms, and found that these surface morphologies usually have good properties of desorption, anti-adhesion and wear resistance [13]. Inspired by the biological surface morphologies, the non-smooth surface has been successfully applied to multiple occasions with relative motion, e.g., bearings [14], cylinder liners [15], mechanical seals [16], and cutting tools [17], to improve the tribological properties [18].…”
Section: Introductionmentioning
confidence: 99%